The Influence of Profitability, Liquidity, Leverage, and Company Growth to Dividend Policy on Agricultural Companies In Indonesia Stock Exchange - Kartika Hendra Titisari, Okta Finingsih, Siti Nurlaela & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Capital Market Issuers in Indonesia are divided into several sectors. One of them isthe agricultural sector. The agricultural sector contributes 1.69% of the total marketcapitalization in the Indonesia Stock Exchange (IDX). The agricultural sector is theowner of the smallest capitalization value compared to other sectors, this is becausethe number of agricultural sector issuers is also smaller than other sector issuers. Sofar the author has not found a research focusing on agricultural sector companies.Population in this research is all agriculture company in Indonesia Stock Exchange,sample is determined by purposive sampling method. This research is focused toknow the influence of financial ratios namely Profitability, Liquidity, Leverage,and Company Growth to dividend policy on agricultural companies in IndonesiaStock Exchange period 2011-2016. The dependent variable in this study isDividend Policy, and the independent variable consists of Profitability, Liquidity,Leverage, and Company Growth. Methods of data analysis using multiple linearregression analysis. The result of multiple linear regression test shows thatprofitability ratio measured by Return on Asset has significant influence to thedividend policy, while other independent variables have no significant influence todividend policy. The result of determination coefficient test shows that 19.8%dependent variable in this research can be explained by the model of this research.Keyword: Profitability, Liquidity, Leverage, Growth, Dividend